Recent R&D Results on Fusion Nuclear Technology for ITER and DEMO Reactor in Japan. (3rd October 2017) - Yamanishi, Toshihiko; Koizumi, Norikiyo; Nakahira, Masataka; Nunoya, Yoshihiko; Suzuki, Satoshi; Tobari, Hiroyuki; Kashiwagi, Mieko; Isono, Takaaki; Inoue, Takashi; Sugimoto, Makoto; Kusama, Yoshinori; Kawamura, Yoshinori; et al.
Abstract: Several key components, such as superconducting coils, remote handling equipment, heating systems, have been designed and manufactured by JADA (Japan Domestic Agency). These activities have been carried out in accordance with the agreed schedule; in collaboration with the ITER organization and other domestic agencies. As a significant technical program using ITER, to design and to manufacture the TBS (Test blanket system), some R&D and design activities have also been conducted in Japan. Under the IFERC (the International Fusion Energy Research Center) projects of BA (Broader Approach) activities, design and R&D activities on fusion DEMO reactor have been carried out. For the DEMO R&D activity, five basic R&D subjects for a DEMO blanket system have been selected, and been studies under close collaborations between EU and JA: structure materials (RAFM steels and SiC/SiC composites), functional materials (tritium breeders and neutron multipliers), and tritium technology. From 2007, the above projects produced a set of fruitful results. A series of advanced technologies for the DEMO blanket system has also been carried out by Universities in Japan. Some significant basic R&D studies have also been carried out under US-JA collaborative program.